2017
DOI: 10.18203/2394-6040.ijcmph20170268
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of cancer diagnosis among gynaecological cancer subjects in a tertiary care centre

Abstract: INTRODUCTIONAmong gynaecological cancers, cervical cancer is one of the most prevalent cancers that afflict women and that lead to deaths worldwide. The data from HBCRs of India has shown that cancer of cervix (28%) and breast (16%) in women are most common and cancer of Head and Neck region constitute about 30% of all cancer in males and females.1 More than 3-8% of ovarian, 0.5-4.8% of corpus uteri, 1-3% of vulvar and gestational trophoblastic tumours are reported in India every year. 2The diagnosis of cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Young women with less education were more anxious compared to educated women. 10 A similar study was conducted in department of psychiatric, NIMHANS, Banglore, Karnataka, by Chaturvedi et al reported the prevalence of depression vary on methodological aspects and vary from 1.5% to 50% (mean 24%; median 22%). The prevalence of depression in patients with cancer varies with cancer site, clinical course, type of treatment, and presence of pain.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Young women with less education were more anxious compared to educated women. 10 A similar study was conducted in department of psychiatric, NIMHANS, Banglore, Karnataka, by Chaturvedi et al reported the prevalence of depression vary on methodological aspects and vary from 1.5% to 50% (mean 24%; median 22%). The prevalence of depression in patients with cancer varies with cancer site, clinical course, type of treatment, and presence of pain.…”
Section: Discussionmentioning
confidence: 75%
“…[7][8][9] Cancer is most stressful condition when a person is histologically confirmed diagnose that often a triggering factor for depression and anxiety. 10 As per the facts and figures of American cancer society, the global cancer burden indicates that cancer accounts for about 1 in every 7 deaths worldwide. In 2030, the globally burden is expected to increase 21.6 million new carcinoma cases.…”
Section: Introductionmentioning
confidence: 99%